Echocardiographic assessment of left ventricular diastolic dysfunction in ischemic heart disease. - Hassan, Affan E.; Sudek, Hanan L.; Abd-alwahab, Taghrid H.; Mohammed, Najeeb H. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: the most common underlying cause of left ventricular (LV) diastolic dysfunction is myocardial ischemia. Diastolic dysfunction has been reported in up to 90% of patients with coronary artery disease.